Experimental Study and Application of Inorganic Solidified Foam Filling Material for Coal Mines - Hu Wen; Duo Zhang; Zhijin Yu; Xuezhao Zheng; Shixing Fan; Bin Laiwang (Advances in Materials Science and Engineering)
Spontaneous combustion of residual coal in a gob due to air leakage poses a major risk to mining safety. Building an airtight wall is an effective measure for controlling air leakage. A new type of inorganic solidified foam-filled material was developed and its physical and chemical properties were analyzed experimentally. The compressive strength of this material increased with the amount of sulphoaluminate cement. With an increasing water–cement ratio, the initial setting time was gradually extended while the final setting time firstly shortened and then extended. The change in compressive strength had the opposite tendency. Additionally, as the foam expansion ratio increased, the solidification time tended to decrease but the compressive strength remained approximately constant. With an increase in foam production, the solidification time increased and the compressive strength decreased exponentially. The results can be used to determine the optimal material ratios of inorganic solidified foam-filled material for coal mines, and filling technology for an airtight wall was designed. A field application of the new material demonstrated that it seals crossheadings tightly, leaves no fissures, suppresses air leakage to the gob, and narrows the width of the spontaneous combustion and heat accumulation zone.